2005
DOI: 10.1007/s00204-005-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

An oral carcinogenicity and toxicity study of senna (Tinnevelly senna fruits) in the rat

Abstract: Senna (Tinnevelly senna fruits), a known laxative derived from plants, was administered by gavage to Sprague-Dawley (Crl:CD (SD) BR) rats once daily at dose levels of 0, 25, 100 and 300 mg/kg/day for up to 104 consecutive weeks. Based upon clinical signs related to the laxation effect of senna, the highest dose (300 mg/kg/day) was considered to be a maximum tolerated dose. Sixty animals per sex were assigned to the control and dose groups. Assessments included clinical chemistry, hematology, full histology (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Chronic use of senna has raised fears of melanosis coli being a premalignant state as well as fears of neuronal damage. Fortunately, long-term studies in rats have shown no evidence of carcinogenicity or enteric nervous damage, but the issues are not definitively settled in humans [19,20]. Carbohydrate osmotic agents work because humans cannot hydrolyze their disaccharide bonds; however, colonic bacteria can hydrolyze this bond, and resultant metabolism produces gas, which can lead to uncomfortable bloating.…”
Section: Traditional Interventions and Their Limitationsmentioning
confidence: 99%
“…Chronic use of senna has raised fears of melanosis coli being a premalignant state as well as fears of neuronal damage. Fortunately, long-term studies in rats have shown no evidence of carcinogenicity or enteric nervous damage, but the issues are not definitively settled in humans [19,20]. Carbohydrate osmotic agents work because humans cannot hydrolyze their disaccharide bonds; however, colonic bacteria can hydrolyze this bond, and resultant metabolism produces gas, which can lead to uncomfortable bloating.…”
Section: Traditional Interventions and Their Limitationsmentioning
confidence: 99%
“…To clarify the detailed mechanisms of skin disruption, we will perform another experiment and administer an anti-tryptase antibody or antioxidant to directly block tryptase or oxidative stress in further research. There have been several reports about the toxicity of chronic senna administration on the intestine2627, however, there is no report about the toxicity on skin. Significant body weight loss was observed after senna treatment, however, weight loss was less likely to have an influence on the skin barrier function because similar tendency was also observed in other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The laxative property of Senna is based on two glycosides sennoside A and sennoside B [11]. The strongest laxative sennosides A and B, shows the lowest toxicity, while fraction that contains rhein 8-glycoside with a minimum efficiency laxative, has increased toxicity [12,13]. Emodin and aloe-emodin showed toxic effects on Salmonella typhimurium, on hepatocytes and fibroblasts from mouse [14].…”
mentioning
confidence: 99%
“…The presence of chemical compounds in the extract depended on the solvent that was used. In addition to that, the incubation process lead to the interaction of the compounds in the extract, as well as to the interaction with their metabolic products, which may have had first an inhibitory effect and later a stimulatory effect on cells at certain extract concentrations [12,13].…”
mentioning
confidence: 99%